Deletion of the novel gene mother cell lysis X results in Cry1Ac encapsulation in the Bacillus thuringiensis HD73 - Wang, Jiaojiao; Yu, Qingyue; Peng, Qi; Slamti, Leyla; Zhang, Ruibin; Hou, Shuo; Lereclus, Didier; Song, Fuping (Frontiers in Microbiology, 2022)
The novel protein MclX (mother cell lysis X) in Bacillus thuringiensis subsp. kurstaki strain HD73 (B. thuringiensis HD73) was characterized in this work. MclX has no known domain and its gene deletion in HD73 resulted in Cry1Ac encapsulation in the mother cell and did not influence Cry1Ac protein production or insecticidal activity. In vitro cell wall hydrolysis experiments showed that MclX cannot hydrolyze the cell wall. In mclX deletion mutants, the expression of cwlC (which encodes a key cell wall hydrolase) was significantly decreased, as shown by the β-galactosidase activity assay. MclX cannot directly bind to the cwlC promoter, based on the electrophoretic mobility shift assay. The cwlC was reported to be regulated by σK and GerE. However, the transcriptional activities of sigK and gerE showed no difference between HD73 and the mclX deletion mutant. It is indicated that MclX influenced cwlC expression independently of σK or GerE, through a new pathway to regulate cwlC expression. mclX deletion could be a new approach for insecticidal protein encapsulation in Bacillus thuringiensis.